2017
DOI: 10.1007/s40261-017-0555-7
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness, Adverse Effects and Drug Compliance of Long-Acting Injectable Risperidone in Children and Adolescents

Abstract: In children and adolescents with conduct disorder, bipolar disorder and schizophrenia who show noncompliance with oral drugs, LAIR may improve treatment compliance. LAIR is a reliable treatment in terms of its effectiveness. Weight-gain, dystonia, and galactorrhea were the adverse effects that were responsible for LAIR treatment cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…While there are no studies looking at LAIAs in youth with ASD specifically, outside of a single case report (Kowalski et al, 2011), work in other psychiatric disorders such as schizophrenia suggest that they are safe and well tolerated, with similar side effect profiles to oral medications. In addition, use of LAIAs is associated with improved adherence and lower overall treatment costs (Ceylan et al, 2017;Lytle et al, 2017). Future description of LAIA use in the context of ASD is needed to inform prescribing practice for patients where oral formulations may be refused or contraindicated.…”
Section: Long Acting Injectable Antipsychoticsmentioning
confidence: 99%
“…While there are no studies looking at LAIAs in youth with ASD specifically, outside of a single case report (Kowalski et al, 2011), work in other psychiatric disorders such as schizophrenia suggest that they are safe and well tolerated, with similar side effect profiles to oral medications. In addition, use of LAIAs is associated with improved adherence and lower overall treatment costs (Ceylan et al, 2017;Lytle et al, 2017). Future description of LAIA use in the context of ASD is needed to inform prescribing practice for patients where oral formulations may be refused or contraindicated.…”
Section: Long Acting Injectable Antipsychoticsmentioning
confidence: 99%
“…For example, patients prescribed SGA drugs often show greater improvement in negative and cognitive symptoms, higher functional capacity, and have better quality of life with lower risks of extrapyramidal side effects (EPS) and tardive dyskinesia (TD) . However, some concerns exist about treatment with risperidone as it may induce side effects such as hyperprolactinaemia , hyperuricaemia , weight gain and dyslipidaemia . Additionally, risperidone could increase the risk of type 2 diabetes .…”
mentioning
confidence: 99%
“…Moreover, paliperidone has less of an effect on liver function, which is much more easily accepted by children and adolescents, who are more sensitive to drug side effects [39,40]. Risperidone was more commonly used in patients with COS. An open controlled study abroad showed that risperidone can significantly improve the positive and negative symptoms of adolescent schizophrenia patients and cause less extrapyramidal reactions than traditional antipsychotics [41,42]. The frequencies of use of aripiprazole and clozapine were not significantly different in the AOS and COS groups.…”
Section: Discussionmentioning
confidence: 99%